I silos granari del Gruppo Ferruzzi. Memoria di uno spazio industriale - Carmen Cecere, Francesca Castanò (OS. Opificio della Storia, 2023)
The article analyses the experience of the Ferruzzi Group of Ravenna and the significant moments of growth and expansion on the Italian and international industrial scene, starting from the 1950s. Through the reconstruction of the events characterising the birth and development of the cereal activities of Serafino Ferruzzi, founder of the company, the aim is to outline the dense network of grain silos built in the main Italian ports, based on the Group’s multiple exchanges with foreign markets, especially South America. Iconic examples of contemporary times, the surviving silos of this industrial enterprise constitute a significant part of port architecture, opening up a broader reflection on their potential uses and future destinies.